UTILIZATION OF ASEPTIC AND ANTISEPTIC STERILIZATION TECHNIQUES BY HEALTHCARE WORKERS - Amrilloeva Gulnora Vokhid kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article examines diverse sterilization techniques, including ultrasonic sterilization, membrane filtration, and the use of antiseptics and disinfectants. It highlights their advantages and disadvantages, as well as their impact on the materials being sterilized. The importance of carefully selecting the appropriate sterilization method based on specific conditions and requirements is emphasized.